The Rise of Statutory Wills and the Limits of Best Interests Decision‐Making in Inheritance. Issue 6 (2nd November 2015) - Harding, Rosie
Abstract : This article addresses 'statutory wills' executed under the Mental Capacity Act 2005 (MCA) for persons with impaired mental capacity. The article provides an overview of the historical development of statutory wills, before exploring their rising contemporary significance. It considers the shift from the previous 'hypothetical substituted judgment' test to the contemporary 'best interests' orientation of the MCA. The article assesses the problems that the best interests approach raises in this area, and its (in)compatibility with the right to equal recognition before the law under the UN Convention on the Rights of Persons with Disabilities, arguing that the pervasive reach of best interests in contemporary mental capacity law requires reconsideration. The paper concludes by suggesting that a more limited framing of the power to execute statutory wills is required in order to appropriately balance the rights of individuals with disabilities with practical considerations around the distribution of assets on death.